2020
DOI: 10.29333/ejmste/8399
|View full text |Cite
|
Sign up to set email alerts
|

Exploring In-Service Mathematics Teachers’ Perceived Professional Development Needs Related to the Strands of Mathematical Proficiency (SMP)

Abstract: The National Research Council developed the concept of mathematical proficiency as being described by five strands: conceptual understanding, procedural fluency, strategic competency, adaptive reasoning, and productive disposition. The purpose of this study is to explore in-service mathematics teachers' perceptions of professional development needs related to the five strands of mathematical proficiency and to investigate the effect of teachers' demographic factors on their perceived needs. Participants includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
1
6
0
1
Order By: Relevance
“…In-service teacher training is one of the most prominent challenges facing the teaching of mathematics in various countries of the world, as it forms the basis for the development of teachers as individuals and groups (Barham, 2020;Copur-Gencturk & Tolar, 2022;Ma'rufi et al 2018;Mok & Park, 2022;Shaqar et al, 2020). These challenges have emerged in Jordan clearly after the change in mathematics textbooks during the last three years, which requires specialized training to familiarize teachers with the standards of change that have occurred, foremost of which is pedagogy and learning with understanding.…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…In-service teacher training is one of the most prominent challenges facing the teaching of mathematics in various countries of the world, as it forms the basis for the development of teachers as individuals and groups (Barham, 2020;Copur-Gencturk & Tolar, 2022;Ma'rufi et al 2018;Mok & Park, 2022;Shaqar et al, 2020). These challenges have emerged in Jordan clearly after the change in mathematics textbooks during the last three years, which requires specialized training to familiarize teachers with the standards of change that have occurred, foremost of which is pedagogy and learning with understanding.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…In addition to, several studies have indicated the importance of considering the training needs of mathematics teachers as well as the significance of developing them professionally (Barham, 2020;Fraihat et al, 2022;Mueller et al, 2014;Omar, 2014).In light of the foregoing discussion, it is necessary to identify these needs, try to find solutions to them, and develop and improve the capabilities of teachers through holding a training program based on the principles of conceptual understanding, with the aim of enhancing pedagogical knowledge of mathematics teachers.…”
Section: Introductionmentioning
confidence: 99%
“…A. Awofala, 2017). Selanjutnya, hasil dari penelitian (Barham, 2020) menemukan bahwa perlu dan pentingnya menyediakan program yang relevan disposisi produktif, diikuti dengan penalaran adaptif, pemahaman konseptual, kompetensi stategis dan diakhiri dengan kelancaran prosedural dalam pengembangan professional seorang guru. Menariknya, hasil penelitiannya merekomendasikan beberapa hal yang perlu dikaji secara mendalam secara kualitatif salah satunya apakah program sarjana membantu mahasiswa dalam memperoleh pengetahuan dan keterampilan berdasarkan strands terbaru yaitu mathematical proficiency dalam pembelajaran matematika?.…”
Section: Gambar 1 Untaian Dari Strands Mathematical Proficiencyunclassified
“…From a componential perspective, mathematical proficiency is seen to comprise five strands (Barham, 2020;Superfine & Li, 2014). The first strand -conceptual understanding -refers to students' understanding of mathematical symbols, visualisation, concepts, operations, and relations.…”
Section: Mathematical Literacy and Professional Competencies Of Mathematics Teachersmentioning
confidence: 99%
“…The domains are specified in 22 indicators in Table 4. Compared with competency models of mathematics teachers in the literature (for example, Barham, 2020;National Council of Teachers of Mathematics, 2000;National Research Council, 2001;Shulman, 1986Shulman, , 1987, the professional competencies identified for Vietnamese teachers in this paper operationalise teachers' MCK and MPCK into domains of teachers' functioning. These domains cover teachers' concrete tasks, namely instructing, designing teaching and learning activities, assessing students' learning outcomes, and supporting students in particular relation to mathematics teaching at the primary school level.…”
Section: Findings Professional Competencies For Primary Schoolteachers Teaching Mathematics In Vietnammentioning
confidence: 99%